The ability to handle conflict is a key factor in managerial success / Kamariah Husin - Husin, Kamariah (Universiti Teknologi MARA Cawangan Pahang, 1991)
Conflict in inevitable in any organisation and can serve as a useful function by stimulating creative solutions to most of the management problems encountered. This paper however attempts to highlight the types of conflict that are normally prevalent in any educational institution. In addition, the causes as well as the role of the Educational managers in handling conflict with particular emphasis both at the interpersonal and the organizational levels are also discussed.